WEDM manufacturing method for noncircular gears, using CAD/CAM software - García-Hernández, César (Strojniški vestnik, 2016)
Noncircular gears are used in several technological applications in order to enhance the performance of different mechanical instruments (flow meters, bikes, internal combustion engines, etc.), in order to unify speed in assembly lines and in research. Noncircular gears are typically manufactured by shaving: milling each tooth or by generation. This requires controlling the geometric and kinematic variables in the process. In this research, a method to manufacture elliptical and oval gears using wire electro-discharge machining (WEDM) is presented. This is a continuous procedure, and its performance is not inferior to the previously mentioned methods. Mathematical models for manufacturing elliptical and oval gears are presented, simulations are carried out, and this method is implemented in a WEDM machine, obtaining two pairs of elliptical and oval gears. This method could be useful in the manufacturing of injection moulds or custom-made metallic gears. Finally, a discussion using bibliographic references is presented about the surface finish and the consequences of using WEDM in comparison to other shaving methods which do not involve a material phase change.
Keywords: CAD/CAM; delovni list; obdelava; zobniki nekrožne oblike; žična elektroerozijska obdelava